Предмет: Математика,
автор: rita728
Решите примеры: первый пример (-4)+(1-3x)при=2,4. второй пример:(x+1)-(-3) при x=1,1
Ответы
Автор ответа:
1
Ответ:
Пошаговое объяснение:
(-4)+(1-3x)=-4+1-3х=-3-3х=-3-3*2.4=-3-7.2=-10.2
(x+1)-(-3) =х+1+3=х+4=1.1+4=5.1
rita728:
там в первом x=2,4
Автор ответа:
0
1) (-4)+(1-3х)=1-3х-4=-3х-3
х=2,4 -3*2,4-3=-10,2
2) (х+1)-(-3)=х+1+3=х+4
х=1,1 1,1+4=5,1
Похожие вопросы
Предмет: Математика,
автор: anastasia8854
Предмет: Информатика,
автор: nastyaaaafff
Предмет: Математика,
автор: 10Emily
Предмет: Математика,
автор: Викториеок